Bioavailability of cellobiose by tolerance test and breath hydrogen excretion in humans - Nakamura, Sadako; Oku, Tsuneyuki; Ichinose, Makoto (Nutrition (Burbank, Los Angeles County, Calif.), 2004)
Prebiotic substances have the property of intestinal fermentation. Cellobiose has a β-1,4 linkage, so it is resistant to hydrolysis by human small intestinal disaccharidase and, hence, reaches the colon undigested. Until this study, it was unclear whether cellobiose has fermentability or bioavailability. The objectives of this study were to clarify whether cellobiose is fermented in the large intestine and to estimate the available energy from cellobiose intake by using tolerance tests and breath hydrogen tests in healthy female subjects. Ten healthy young women (20.5 ± 2.1 y) who did not develop diarrhea after ingesting 30 g of cellobiose in a previous experiment were recruited. Tolerance tests and breath hydrogen tests for 25 g of cellobiose or glucose were carried out at least 2 wk apart. Blood samples were collected before and at 30-min intervals up to 3 h after ingestion. Breath gas samples were collected simultaneously before and at 30-min intervals up to 6 h after ingestion of cellobiose or glucose. Blood glucose and insulin levels and the concentration of breath hydrogen were analyzed. When 25 g of cellobiose was ingested, there was no increase in blood glucose or insulin secretion, but these markers increased remarkably with glucose ingestion. The excretion of breath hydrogen gas after cellobiose ingestion was significantly greater than that after glucose ingestion. Orally ingested cellobiose was well fermented in human large intestine, and its available energy was estimated to be about 2 kcal/g.